A Study on the relationship between Environmental Education and Rural Education (Research, Society and Development, 2020)
Brazilian history shows that, for many years, rural education was not even mentioned in educational norms, causing the peasantry to not recognize itself as a subject of rights and obligations. Thus, it is essential to awaken the sense of belonging of the rural subject through the integration between the contents of environmental education with the precepts of rural education. Considering that education is one of the mechanisms of social development of human beings, it must be promoted in an effective, contextualized and meaningful way for the transformation of the society in which the subject is inserted. Therefore, this study aimed to seek theoretical foundations that conjecture on the inference of the transdisciplinary work of the contents of environmental education and rural education in changing the peasant's behavior and quality of life. Thus, a bibliographic review was carried out which included studies on environmental education, rural education and their interlocutions. Finally, it was realized that for environmental education to be effective in rural schools, it is necessary to develop the student's criticality, based on the cognitive and political maturation of all those involved in the teaching-learning process.